2020
DOI: 10.1101/2020.11.24.20238063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physical exercise is a risk factor for amyotrophic lateral sclerosis: Convergent evidence from mendelian randomisation, transcriptomics and risk genotypes

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a universally fatal neurodegenerative disease. ALS is determined by gene-environment interactions and improved understanding of these interactions may lead to effective personalised medicine. The role of physical exercise in the development of ALS is currently controversial.MethodsWe dissected the exercise-ALS relationship in a series of two-sample Mendelian randomisation (MR) experiments. We then we tested for enrichment of ALS genetic risk within exercise-asso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…However, once the disease is developed, exercise exerts benefits on patients as it improves their functional scores [183]. Besides, a study using big data and Mendelian randomization approach has found an association between genetic liability to strenuous sport exercise and ALS risk [184], supporting the idea of a vulnerability to sALS in the context of high levels of physical activity. This indicates that forced and excessive usage of skeletal muscle resources during early and mid-life might be a pathogenic factor in genetically predisposed individuals, but the underlying mechanisms that account for this association are still far from being delineated.…”
Section: Muscle Exercising and The Risk Of Alsmentioning
confidence: 98%
“…However, once the disease is developed, exercise exerts benefits on patients as it improves their functional scores [183]. Besides, a study using big data and Mendelian randomization approach has found an association between genetic liability to strenuous sport exercise and ALS risk [184], supporting the idea of a vulnerability to sALS in the context of high levels of physical activity. This indicates that forced and excessive usage of skeletal muscle resources during early and mid-life might be a pathogenic factor in genetically predisposed individuals, but the underlying mechanisms that account for this association are still far from being delineated.…”
Section: Muscle Exercising and The Risk Of Alsmentioning
confidence: 98%
“…The heterogeneities were quantified by the Cochran Q statistic; p > .05 was considered to indicate that there was no heterogeneity in the included instrumental variables, and the influence of heterogeneity on the estimation of causal effects could be ignored. If the heterogeneity existed, then the IVW (multiplicative random effects) was used to calculate the effect size 47,48 . According to the abovementioned MR assumptions, if a GIV directly influenced the outcomes without affecting the exposure, the fundamentals of the MR method were violated.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded SNPs with r 2 < 0.001 and kb > 10000 kb using linkage disequilibrium (LD) analysis, which means removing SNPs with an r 2 greater than 0.001 in the 10,000kb range with the most signi cant SNP. 27 To alleviate weak instrument bias, we calculated F-statistics for each SNP and excluded SNPs with F-statistics less than 10. 28 When the F statistic is less than 10, we consider the genetic variation used to be a weak instrumental variable, which may bias the results to some extent.…”
Section: Snps For Exposuresmentioning
confidence: 99%